O7 Investigating IDA: large-scale data showing persistent gaps at the front door. (19th June 2022) - Howell, George; Thumbe, Akanksha; Adderley, Nicola; Iqbal, Tariq; Lasserson, Daniel; Nirantharakumar, Krish; Quraishi, Mohammed Nabil; Sapey, Elizabeth; Sharma, Neel; Bhala, Neeraj
Abstract : Introduction: Iron deficiency anaemia (IDA) can be a sign of serious underlying disease but often overlooked. Recently updated guidelines of the British Society of Gastroenterology (BSG) recommend male and postmenopausal female patients with IDA should be screened for coeliac disease and undergo dual endoscopy (or CT). Aims This project looked to assess current adherence to these guidelines at the Queen Elizabeth Hospital in Birmingham. Methods: A retrospective audit was performed using health informatics for patients who attended AMU/CDU from April 2018 to March 2021. The number of patients with IDA in this time frame was identified. A further analysis of this group was made to determine the proportion of patients with IDA who had IgA TTG measured as well as those who had OGD and colonoscopy/CT colonoscopy requested. Results: There were 67797 patients in this study period. 32422 (47.8%) were anaemic (Hb < 120g/dl for women, <130g/dl for men as per WHO guidelines) of which 6357 (19.6%; 9.38% of total) had a microcytic anaemia (MCV <83 as per University Hospitals Birmingham laboratory reference range). Ferritin was tested in 3337 (52.5%) of this group, and of those, 1041 (31.2%) were found to have overt IDA (ferritin <30 μg/mL). Rate of investigation: The patient cohort with confirmed IDA comprised 334 males (32.0%), 556 post-menopausal females (53.4%, defined as age ≥45) and 151 pre-menopausal females (14.5%). A further analysis was made to explore how male and postmenopausal female cases were investigated, and if the rate of investigation was affected by the COVID-19 pandemic from 1 st March 2020 onwards in this subgroup. Results are shown in the table below. In general, only a minority of patients underwent further investigation with males more likely to undergo OGD than females. Surprisingly, apart from increased TTG check latterly, little difference was seen after onset of the COVID-19 pandemic. Conclusions: This large-scale study found that only a small minority of patients with IDA underwent further investigation. Whilst the study period includes the pandemic era, our results don't suggest this made a significant impact on practice. Nevertheless, these findings indicate a strong need for increased awareness and quality improvement about optimising IDA investigation according to BSG guidelines.